The Analysis of Inequality on Economic Growth in Indonesia - Fitrawaty Fitrawaty (RIRAI Publisher, 2020)
Development is carried out to improve people's welfare, so that economic growth and an even distribution of income are needed. Rapid economic growth that is not balanced with equal distribution, will lead to regional imbalances. The objectives of this study are to; (1) to analyze the factors causing inequality on economic growth in all provinces in Indonesia; (2) to analyze the largest contributor to development inequality between provinces in Indonesia, (3) to form a model of development inequality and economic growth for each province and Indonesia (4) to generat ideas or ideas for solutions to control development inequality and economic growth in Indonesia. The variables studied are the wiliamson index, human development index, unemployment and the General Allocation Fund for each province in Indonesia in 2010-2017. The data observed are primary data and secondary data from various related agencies, such as Bank Indonesia, Statistics Indonesia, Ministry of National Development Planning of the Republic of Indonesia and Ministry of Finance Indonesia. Before being analyzed, the data will pass through the next classical assumption test stage with the Panel Data Model. The results showed that the unemployment rate had a negative and significant effect, while General Allocation Fund and HDI had a positive and significant effect on the level of inequality in Indonesia.